ANALYSIS OF ENGLISH READING SKILLS OF ELEMENTARY SCHOOL STUDENTS: A STUDY IN MUHAMMADIYAH 1 BENGKULU ELEMENTARY SCHOOL - Solehan; Finessa Salsabila (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research endeavor seeks to critically examine the English reading competencies of elementary school learners enrolled at SD Muhammadiyah 1 Bengkulu. The investigation delves into the levels of reading proficiency exhibited by students, the obstacles they encounter, the methodologies they adopt, and the contributions of educators and guardians in facilitating the advancement of English literacy. A qualitative research methodology is employed in this study, encompassing classroom observations, comprehensive interviews with students from grades 4 through 6 and their English instructors, alongside the analysis of relevant documents such as instructional materials, lesson plans, and student evaluation outcomes. Participant selection is executed utilizing purposive sampling methods, with criteria established for students who have engaged in English studies for no less than two years, exhibit diverse proficiency levels, and possess parental authorization. Data is subjected to thematic analysis, which encompasses familiarization with the dataset, coding, theme identification, reviewing and refining themes, as well as naming and defining these themes. This study adheres to ethical research tenets, which include informed consent, confidentiality and anonymity, protection against harm, the entitlement to withdraw, and reciprocal benefits. The anticipated outcomes of this research are expected to yield comprehensive insights into the intricacies of teaching English reading at the elementary level, identify efficacious practices to bolster EFL students’ reading competencies, and provide recommendations for the enhancement of more effective English programs at SD Muhammadiyah 1 Bengkulu and other analogous elementary institutions. Keywords: EFL Reading Skills, Elementary School